2007
DOI: 10.4028/www.scientific.net/kem.361-363.487
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Titanium Oxide/Titanium/Plastic Composites

Abstract: Titanium oxide/ titanium/ plastic composite implants were formed by coating commercially pure titanium thin films on the surfaces of plastic cylinders by DC magnetron sputtering method. The composite is uniformly formed and the surface of the composite implant is smooth. The implants in rat tibias were not broken and the films on the surfaces of the samples did not decompose. The samples with bone were able to cut by diamond knife and observations between bone and titanium oxide on titanium by TEM succeeded. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…In this study, we formed titanium nitride film on titanium interlayer by the magnetron DC sputtering machine [5][6][7] without substrate heating or reactive nitrogen gas. The machine has the planar magnetron sputtering system and the thermal influence on the sample due to the magnetron DC plasma is small [5,8]. By using this method, even if the substrate contains a harmful element, it is difficult to diffuse into the film.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we formed titanium nitride film on titanium interlayer by the magnetron DC sputtering machine [5][6][7] without substrate heating or reactive nitrogen gas. The machine has the planar magnetron sputtering system and the thermal influence on the sample due to the magnetron DC plasma is small [5,8]. By using this method, even if the substrate contains a harmful element, it is difficult to diffuse into the film.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to observe the interactions between titanium oxide and cells on cp titanium, because cp titanium implants are not transparent. In our previous studies, we reported the experimental implantation of titanium oxide/ titanium/ plastic materials in a mouse and observation of the interaction between the titanium implant surface and the living bone [2,3,4]. The implant was easy to cut by a diamond-blade microtome, and titanium osseointegration could be observed by light microscopy.…”
Section: Introductionmentioning
confidence: 99%